Editorial - Granados, Carlo (GIST – Education and Learning Research Journal, 2022)
Welcome to a new issue of GiST Journal! This edition incorporates contributions about Content Language Integrated Learning, Teachers’ Cognitions, and ICTs, among many other aspects. This issue reflects all the learning researchers and teachers have gained during the pandemic in the implementation of ICTs for teaching languages. Silva-Perdomo, Duero-Naranjo and Castañeda report a narrative study with the aim understanding students’ experiences in English courses while using ICT. Also, Çakan Uzunkava and Gül report a study aimed to evaluate the contribution of the activities prepared with Web 2.0 technologies in the achievement of music lessons. Additionally, it aimed to understand the perceptions towards the use of technologies in different areas of learning. Regarding methodological interests, Mosquera-Pérez contributes a theoretical reflection upon Content Language Integrated Learning (CLIL) and the challenges regarding its implementation in Colombia. Also, Roberto, Arias-Rodríguez and Herreño reports case study which aim was promoting critical thinking skills in Law students by using virtual tools. Yarim, Yildirim, and Akan’s phenomenological study explores the factors behind teacher candidates’ motivation concerning the profession. Adem and Berkessa contribute a mixed-method study whose goal was exploring teachers’ cognitions in relation to teaching speaking. Least but not least, Mora questions us about the frameworks we have used for the teaching and learning of English in Colombia, ambitiously proposing the move from English as a Foreign Language (EFL) to English as a Colombian Language (ECL) and, finally, to Colombian English (CE) for the benefit of equity. We invite ELT scholars in Colombia and abroad to continue disseminating the results of their research and reflections and we thank the continuous support given by the members of our editorial and scientific committees, authors, and readers.